Diagnozowanie utraty wartości aktywów w kontekście rachunkowości odpowiedzialności opartej na działaniach - komunikat problemu - Karmańska, Anna (The Diagnosis of the Depreciation of Assets Value in the Context of Activity-Based Accounting, 2005)
This text indicates the influence of premises resulting from operational management in business entity on recognizing its assets as useful and able to provide economic benefits. The presentation of conceptual frames for analysis of this issue consists of several steps. The first step highlights the significance of responsibility accounting in operational management in business entity. The second step locates in management a new main trend, called process management. The third step, concentrating on resources management, which is one of elements of process management, directly refers to possibilities of connecting process management with an evaluation of appearance of permanent loss in value of some of entity's assets. The fourth step is a presentation of conceptual relationship between activity based budgeting and estimation of economic benefits attributed to particular assets. This step also underlines the significance of these estimation in entity's property valuation for balance purposes. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 258-264